Brain Types and Wages - Nick Drydakis (Institute for the Study of Labor (IZA), 2015)
We examine the association between brain types and wages using the UK Behavioural Study dataset for the period 2011 to 2013 (four waves). By applying Empathising-Systemising Theory (E-S), the estimations suggest that, for men and women, systemising traits are associated with higher wage returns than empathising traits and that a Type-S brain (also known as a Male-brain, entailing greater skills in directing systems) is associated with higher wage rewards than a Type-E brain (also known as a Female-brain, entailing more social skills). In addition, wage decompositions suggest that systemising traits can explain greater differences in the assigned gender wage gap compared to empathising traits. Interestingly, the estimations suggest that the wage returns of empathising and systemising traits vary by occupation and that each trait might provide an absolute wage-return advantage in certain occupations. Whilst men and women in certain occupations might face positive wage rewards when they have empathising and systemising traits and work atypical of those common to their gender, it would appear that evaluating individuals' empathising, systemising and brain type is perceived to be important for employees' wage returns.
Keywords: J24; J31; 330; segregation; empathising-systemising theory; brain-type; wages; wage-gap